Pengaruh Doping Terhadap Performa Atlet Dan Dampak Dalam Dunia Olahraga - Nimrot Manalu; Meisiska Saragih; Daniel Turnip; Pedro Sinabutar; Ferdinando Sirumapea; Agnes Sirait; Azzahra Nur Syifa; Oswald Krisna; Miftahul Ihsan; Rizky Presto (CV. ITTC INDONESIA, 2025)
Doping is the use of certain substances or methods to enhance an athlete's performance unnaturally. This practice has become a serious issue in the world of sports because of its impact on athlete health and competition ethics. This study aims to examine the effects of doping on athlete performance, its health impacts, and prevention efforts. The research method uses literature studies by analyzing various scientific sources related to doping. The results of the study show that doping can increase strength and endurance, but has serious side effects such as cardiovascular and psychological disorders. Prevention efforts by anti-doping agencies continue to be tightened to maintain the integrity of sports.